Analisis Perubahan Kemampuan Kognitif Siswa Melalui Pembelajaran Probing Prompting Pada Materi Alat-Alat Optik - Putri Rashinta Damayanti; Farida Huriawati (JEMS: Jurnal Edukasi Matematika dan Sains, 2021)
This study aims to obtain information about changes in students' cognitive abilities from before and after participating in learning using the probing prompting learning model. This type of research is qualitative with a descriptive approach. The design of this research is One Group Pretest Posttest. The research subjects were 68 students from class XI IPA 3 and XI IPA 4 at SMAN 6 Madiun. Students are divided into three categories, namely high category, medium category and low category. Each consisted of high category 11 students, medium category 38 students and low category 19 students. The results showed that there was a change in the cognitive abilities of high category students in the cognitive domains C1-C4 but not too significant. The category is experiencing significant changes in cognitive abilities in the C3 and C4 cognitive domains. While the low category experienced significant changes in all cognitive domains in C1-C4.   Keywords : cognitive ability, probing prompting and optic